Thermal and phase stability of nano-layered ceramics – M[subscript]n[subscript]+[subscript]1AX[subscript]n phases - Pang, Wei Kong (Curtin University, 2010)
M[subscript]n[subscript]+[subscript]1AX[subscript]n (M: early transition metal, A: group-A element, X: carbon or nitrogen, n: an integer between 1-3) phases are a group of newly developed materials with the advantages of both metals and ceramics, resulting in low density, low hardness, good machinability, high strength and high Young’s modulus at high temperature, high chemical resistance, excellent thermal shock resistance, as well as thermal and electrical conductivity. This salient combination of properties makes these materials potential candidates in diverse field of applications, especially in high temperature and extreme environments.This study focussed on the characteristics of oxidation behaviour and thermal stability of MAX phases at elevated temperatures in air and in vacuum, respectively. Ex-situ and in-situ experiments have been conducted to evaluate the influence of temperature on the thermal and phase stability of MAX phases. The specific techniques employed were grazing-incidence synchrotron radiation diffraction (GISRD), multiple-wavelength synchrotron radiation diffraction (MWSRD), secondary-ion mass spectrometry (SIMS), nuclear magnetic resonance (NMR), both in-situ constant-wavelength (CW) and time-of-flight (ToF) neutron diffractions (NDs), as well as scanning electron microscopy (SEM) and transmission electron microscopy (TEM).The use of GISRD was used as it provides near-surface analysis of the oxidised and thermal-dissociated products. It also has the potential of mapping compositional depth profiles by altering the grazing incidence angles for the ultra-bright, high-energy synchrotron measurements. The use of MWSRD was used as it performs similarly to GISRD and provides supplementary information on compositional depth profiles.The use of SIMS was also considered. It is destructive to the samples but can provide elemental near-surface analysis of the oxidised products by sputtering out the surface atoms of the sample under high energetic bombardment of primary ions (Cs+). Given that SIMS does not have the limitations of GISRD (where only crystalline phases are detectable), it can offer an image of the inward diffusion of oxygen and outward diffusion of atoms from the sample (including those that are not in a crystalline form), which occurred during oxidation.The use of NMR – both solid state [superscript]2[superscript]9Si- and [superscript]2[superscript]7Al-magic angle spinning (MAS) NMR – was also considered. This provides information on bonding characters of oxides (silica and alumina) formed during oxidation and the results have confirmed the existence of amorphous oxides during low temperature oxidation.Together with NMR spectra, both compositional and elemental depth profiles helped in understanding the formation of oxide layers of MAX phases in order to discover the mechanism of oxidation in air at elevated temperatures.The use of ND was also considered. Both CW- and ToF-ND provide the in-situ phase transition analysis qualitatively and quantitatively during vacuum annealing up to 1800 °C. Arrhenius’ and Avrami’s equations have been used to determine the apparent activation energy and model the mechanism for thermal dissociation of MAX phases in vacuum at elevated temperature.Electron microscopy, both SEM and TEM, has been considered. The micrographs and electron diffraction patterns provide supplementary information to the important findings of GISRD, SIMS, NMR, as well as ND.The combination of GISRD/WMSRD, SIMS, NMR, ND, SEM and TEM was found to be excellent for providing comprehensive information on the characterisation of nano-layered MAX phases. The results will optimise the MAX phases to be applied in diverse fields.